Glaucoma Prevalence and Glaucoma Surgical Considerations in Prosthetic Replacement of the Ocular Surface Ecosystem Device Use. Issue 2 (February 2022) - Duong, Andrew T.; Ertel, Monica K.; Van Tassel, Sarah H.
Abstract : Objectives: The purpose of this study was to identify patients with glaucoma and corneal/ocular surface disease who have been fit with Prosthetic Replacement of the Ocular Surface Ecosystem (PROSE; BostonSight, Needham, MA) devices and to understand the PROSE device fit experience in patients with glaucoma at Weill Cornell Medicine (WCM). Methods: This is a retrospective chart review of patients older than 18 years who underwent PROSE device fitting at WCM. Records were reviewed for demographic information and ophthalmic variables. Descriptive statistics were performed. Results: Between 2011 and 2017, 281 patients underwent PROSE device fitting at WCM, of whom 24 patients (8.5%) had a glaucoma diagnosis and 17 patients (6.0%) were identified as glaucoma suspect. Ocular surface disease was the most common indication for PROSE device wear (58.3%). Five patients had a history of incisional glaucoma surgery in the eye undergoing PROSE device fitting: three valved glaucoma drainage implants and two trabeculectomies. Three of these eyes were successfully fit with PROSE devices. Conclusions: Patients fitted with Prosthetic Replacement of the Ocular Surface Ecosystem devices at WCM had a higher prevalence of glaucoma than in the general population. Among patients with incisional glaucoma surgery, PROSE device fitting was challenging, with a 40% failure rate.